Identifikasi Biaya Operasional dan Resiko Kredit Pada Penjualan - Aludin; Mery Amelia (Asosiasi Ahli Administrasi Indonesia, 2020)
The purpose of this research is to identify the influence of operating cost and credit risks in the sale of X company. This research uses the descriptive method. The data are analyzed using multiple linear regression. The population of this research is financial statements from 2008 to 2015. The reports used as samples are administration fee reports, marketing costs report, and all bad loans in PT X from 2008 to 2015. The results of the study show that operational costs variable have a positive effect on sales, while credit risk as measured by Non Performing Loans has a negative effect on sales. This means that if credit risk increases, the number of sales will increase. On the other hand, if credit risk decreases, profitability will decrease.